Bibliometric Analysis of Research on Multicultural Education in Google Scholar Database (2018-2022) - Hatma Heris Mahendra; Bunyamin Maftuh (Dinamika Ilmu, 2023)
The implementation of good multicultural education in schools will be able to have a positive influence on fostering multicultural traits in students. With the development of science and technology, there will be more and more challenges in research on multicultural education, but it is not yet known whether research on multicultural education is still in demand in educational research. This study utilized the VOSViewer software to conduct a bibliometric analysis of articles available in the open-source Google Scholar database for a 5-year period (2012-2021). The research methodology involved using bibliometric analysis with VOSViewer mapping on the Google Scholar database. From the search results with the keyword multicultural education, it was found that there were 617 relevant articles published in the last 5 years. It can be concluded that from the results of the mapping it appears that the field of multicultural education is still open to carrying out newer research linked to other terms so that newer and up-to-date research can be carried out. The implementation of research with the theme of Multicultural Education is still very broad and can be carried out by connecting it to various new terms such as 21st learning skills, social conflict, conflict-based management, diversity and global education, and other terms.